PERAN GALERI INVESTASI SYARIAH BURSA EFEK INDONESIA (GIS BEI) IAIN BENGKULU DALAM MENINGKATKAN LITERASI PASAR MODAL (Studi Kasus Masyarakat Sumur Dewa Air Sebakul) - LUCY AUDITYA (Al-Intaj : Jurnal Ekonomi dan Perbankan Syariah, 2019)
The purpose of this study was to find out how the role of the Indonesian Stock Exchange Islamic Investment Gallery (GIS BEI) IAIN Bengkulu Gallery in improving Capital Market literacy in the Community thus encouraging an increase in fraudulent investment fraud. This study uses descriptive qualitative methods. The data used are primary data and secondary data. Data collection techniques used were interviews, observation, and documentation in accordance with the problems studied, and data analysis techniques using the Miles and Huberman models. The results of this study reveal that the IDX Investment Gallery concept of 3 in 1 which is a collaboration between the IDX, Universities and Securities Companies is expected not only to introduce the Capital Market from the theoretical side but also the practice. The existence of the IDX Investment Gallery is expected to provide mutual benefits to all parties so that the dissemination of capital market information is on target and can provide optimal benefits for students, economic practitioners, investors, capital market observers and the general public in the surrounding areas both for socialization and education purposes / capital market education as well as for economic interests or investment alternatives to avoid fraudulent investment fraud.